Would it be possible to trade landscape values? An application of agricultural landscape values - Grammatikopoulou, Ioanna; Pouta, Eija; Salmiovirta, Maija (it, 2011)
Agri-environmental policy measures are insufficient to ensure the provision of agricultural landscape attributes that would follow peoples preferences. The study suggests a landscape value trade (LVT) scheme to be implemented locally so as to ensure the supply of environmental services demanded by local citizens. The feasibility of LVT, a "user-financed" payment for environmental services (PES) scheme, is analyzed in a local case from the southern part of Finland. We examine both the land-owners (sellers) as well as the residents (buyers) dispositions. Almost half of the land-owners were hesitant towards LVT and for most of the attributes improvement they demanded compensation larger than their expenses. To examine buyers preferences for certain landscape attributes and also the existence of heterogeneity we employed a random parameters logit (RPL) with interactions model. Buyers preferences were found to be spatially heterogeneous and thus transaction costs are expected to significantly determine the LVT performance. However, the LVT plan that would incorporate the most significant landscape attributes, i.e. presence of grazing animals, buffer water zones managements on a natural state and renovation of production buildings, was evaluated to be feasible to put into practice while the aggregate benefits were almost twice as much as the anticipated costs.
Keywords: Ma; kustannus-hyötyanalyysi; maisemasuunnittelu; maatalousmaisema; agricultural landscape; cost benefit analysis; environmental services; logit model; cost-benefit